Chemistry : General, organic and biological chemistry - Timberlake, Karen (New York ; London : Prentice Hall, 2010)
For two-semester courses in General, Organic, and Biological Chemistry taken by allied health majors. Also suitable for one-semester courses with a comprehensive approach -- A clear and friendly writing style, student-focused approach, and real-world, health-related applications have made Karen Timberlake a best-selling author in the allied health market. General, Organic, and Biological Chemistry: Structures of Life, Third Editionbreaks chemical concepts into bite-size pieces, with a step-by-step approach that provides clear and thorough understanding; conceptual questions at the end of each chapter test student comprehension of the material. The Third Edition is available with MasteringChemistry$1!"(B, the most advanced chemistry homework and tutorial system available.s
Measurements -- Energy and Matter -- Atoms and Elements -- Nuclear Chemistry -- Compounds and Their Bonds -- Chemical Reactions and Quantities -- Gases -- Solutions -- Chemical Equilibrium -- Acids and Bases -- Introduction to Organic Chemistry: Alkanes -- Alkenes, Alkynes, and Aromatic Compounds -- Alcohols, Phenols, Thiols, and Ethers -- Aldehydes, Ketones, and Chiral Molecules -- Carbohydrates -- Carboxylic Acids and Esters -- Lipids -- Amines and Amides -- Amino Acids and Proteins -- Enzymes and Vitamins -- Nucleic Acid and Protein Synthesis -- Metabolic Pathways for Carbohydrates -- Metabolic Pathways and Energy Production -- Metabolic Pathways for Lipids and Amino
Includes index.
"Pearson international edition"--Cover.
1
Keywords: Chemistry -- Textbooks; Chemistry, Organic -- Textbooks; Biochemistry -- Textbooks